Multiple scattering in the presence of absorption: A theoretical treatment for quasi one-dimensional systems - Bruce, N; Chalker, J (1996)
We consider propagation of waves in a disordered medium, extending the treatment of quasi one-dimensional systems, due to Dorokhov and to Mello et al to include absorption. In particular, we obtain within this approach the probability distribution of the reflection matrix for a semi-infinite system, as a function of the ratio of the mean free paths for absorption and scattering. © 1996 IOP Publishing Ltd.